Descripción de los servicios en salud bucal registrados en los rips del municipio de armenia, año 2017 (2020)
The present investigation is linked to the line of investigation of Public Health of the Faculty of Dentistry of the Antonio Nariño University; which specifically addresses the description of oral health services registered in the RIPS of the municipality of Armenia, during the period 2017. Concurrent with the concern about the proposed investigation, the existing documentary review was addressed in relation to the description of the oral health services registered in the RIPS of the municipality of Armenia, in such a way that the necessary contributions to raise the problem are obtained, justification, formulation of objectives and a theoretical reference that indicate what to do in the research process in relation to the Unique Codes of Health Procedures 2019. The collection and analysis of data, contributes to deepen the knowledge about the Unique Codes of Health Procedures 2019 and its relationship, with one or more variables in a population, is of great interest to institutions providing health services and to staff assistance, taking into account that the results of the research can generate improvement programs. The development of the objectives was approached from the collection of the information going to the secondary source, through the analysis of the RIPS methodologically validated by the researchers, in such a way that they allow the quantification of the data and later the description of the variables and their relationship under study.